A simplified protocol for culture of murine neonatal cardiomyocytes on nanoscale keratin coated surfaces. (1st April 2017) - Jain, Aditi; Ravi, Venkatraman; Muhamed, Jaseer; Chatterjee, Kaushik; Sundaresan, Nagalingam R.
Abstract: Objective: We aim to develop a simple, efficient and cost-effective protocol for culturing the neonatal cardiomyocytes using keratin derived from human hair, which can be used for studying cardiac hypertrophy in vitro . Methods: Keratin was extracted from human hair and applied as nanoscale coating onto the culture dishes. Physical parameters such as surface morphology and roughness of the coating were studied by SEM and AFM. Cardiomyocyte specific markers were assessed by immunofluorescence. Signaling pathways activated in hypertrophy were analyzed by western blotting and changes in the expression of fetal genes were analyzed by qPCR. The changes in the calcium fluxes were observed microscopically using Fluo-4. Results: Keratin coated surfaces displayed a uniform coating and comparable roughness across dishes. Our optimized protocol for isolating cardiomyocytes yielded up to 10 6 cells per heart. Characterization of cardiomyocytes with specific markers revealed that they can attach, grow and show spontaneous contractions on keratin-coated substrates similar to fibronectin-coated surfaces. Phenylephrine (PE) treated cardiomyocytes grown on keratin-coated substrates exhibited increased cell size, sarcomere organization and perinuclear ANP expression indicating the development of cardiac hypertrophy. In addition, we observed increased activation of Akt and ERK pathways, induction of the fetal genes and increased protein synthesis upon PE treatment, which are characteristics of cardiomyocyte hypertrophy. The protocol was extended to mouse cardiomyocytes and found to show similar results upon examination. Conclusion: We demonstrate that keratin can act as an efficient yet cost effective alternative substrate for the attachment, growth and differentiation of neonatal murine cardiomyocytes.